Promoting Women's Leadership: What Works, What Doesn't, and What's Missing - Francesca Bramucci; Ana Maria Munoz Boudet; Mariana Viollaz (Institute of Labor Economics (IZA), 2025)
Women remain underrepresented in leadership worldwide. Across politics, business, and community organizations, they face barriers limiting access to leadership roles and influence in decision-making. This paper groups these barriers into opportunity, motivation, and capability, and reviews global evidence on interventions to address them. It assesses the effectiveness of these approaches, how descriptive representation (holding a leadership position) translates into substantive representation (influencing decisions), and unintended consequences. Quotas can increase women's descriptive representation when well designed and enforced. Role model interventions may motivate participation, mainly in politics, though evidence is mixed elsewhere. Training, mentorship, and organizational reforms show context specific results, often supporting career progression rather than leadership attainment. Greater numerical representation does not always yield substantive influence. Outcomes depend on institutional context, gender norms, and complementary support. Advancing women's leadership requires strategies that address multiple barriers and further research on how representation translates into real influence.
Keywords: J16; J24; D72; M14; 330; leadership; gender; descriptive representation; substantive representation; quotas